Location Choices of Multinational Firms: The Case of Mergers and Acquisitions - Habib Zitouna; Jean-Louis Mucchielli; Olivier Bertrand (Hamburg Institute of International Economics (HWWA), 2004)
This article examines the location choices of cross-border Mergers and Acquisitions (M&A) between OECD members firms in the 1990`s. In addition to traditional determinants of FDI, we estimate the impact of specific factors affecting the M&A location pattern. Two distinct econometric methods are implemented: the conditional logit and the count model (Poisson or negative binomial model). In spite of the use of alternative econometric methods, we find that the supply of target firms (captured by market capitalization and privatization activity) constrains the location of M&A. However, is it not the only determinant of location: market size, labor costs, market access and financial openness play a positive and significant role on the M&A location. A bandwagon effect is also observed. In the opposite, the corporate tax rate and the productivity decrease the probability to attract M&A. Cultural and geographic distances and differences in legal rules also exert a negative significant impact on M&A strategies. Only the ownership structure has contrasted results.
Keywords: R3; L1; F23; 330; Foreign Direct Investment; Merger and Acquisition; Location; conditional logit; count model; Multinationales Unternehmen; Übernahme; Direktinvestition; Standortwahl; Standortfaktor; Schätzung; Theorie; OECD-Staaten